A novel synergistic confinement strategy for controlled synthesis of high-entropy alloy electrocatalysts. Issue 21 (15th February 2021) - Li, Huining; Zhu, Han; Shen, Qikai; Huang, Shaoda; Lu, Shuanglong; Ma, Piming; Dong, Weifu; Du, Mingliang
Abstract : A synergetic confinement method is proposed for high-entropy alloy nanoparticles (HEA-NPs) synthesis. Carbon nitride matrix and polydopamine coating contribute to the homogeneous NPs formation. The HEA-NPs show superior electrocatalytic property. Abstract : We report a synergistic confinement strategy for the synthesis of high-entropy alloy nanoparticles (HEA-NPs). The carbon nitride substrate and polydopamine coating layer synergistically confine the growth of NPs and contribute to the formation of homogeneous HEA-NPs. The HEA-NPs exhibit superior electrocatalytic performance for oxygen reduction and evolution reactions. This work demonstrates the great potential of HEA-NPs for electrocatalysis.